The benefits of adding eggshells to the porosity and flexural strength of temporary fixed denture in long-term-use - Ricca Chairunnisa; Umaiyah, Triani; `, Syafrinani (Indonesian Journal of Prosthodontic, 2024)
ABSTRACTBackground: Temporary fixed partial dentures (FPD) are worn for a limited time before definitive FPD, but in some cases like crown lengthening procedures, supra structure implant, temporomandibulardisorders, and endodontic treatment, require long-term temporization. Polymethyl Methacrylate (PMMA)which is commonly used for temporary fixed dentures has weaknesses, namely porosity, low value offlexural strength and impact, low abrasion resistance, ease of fracture, shrinkage after polymerization, andleaves monomer residue, so modification is needed with the addition of reinforcing materials. Reinforcement like fiber filler is difficult to absorb resin monomers causing space between the surfaces of fiber and polymer matrix thereby reducing the mechanical strength of the resin. Eggshell is a natural source of calcium, has the potential as a biocompatible material with an economical price, and is easy toobtain as an alternative material for PMMA reinforcement. Objectives: This paper discusses the long-term use of temporary FPD, PMMA as a temporarily fixed material, and the benefit of eggshell waste to porosity and flexural strength of PMMA materials. Conclusion: The addition of eggshell to PMMA for temporary fixed restoration could decrease porosity and increase the flexural strength of PMMA material because it contains calcium carbonate so that it could be used for the manufacture of provisional fixed restoration which requires long-term useKeywords: temporary fixed denture, polymethyl methacrylate, eggshell, porosity, flexural strength